A New Mitigation Measure to Counter Thermal Instability of Air-Cooled Embankment in Sandy Permafrost Zones of Tibet Plateau - Minghao Liu; Jing Luo; Liang Zhang; Xin Ju (Advances in Materials Science and Engineering)
A crushed-rock revetment (CRR) with high permeability that can be paved on embankment slopes is widely used to cool and protect the subgrade permafrost. In this study, a traditional CRR over warm permafrost was selected to investigate its cooling characteristics based on the ground temperature observed from 2003 to 2014. A new mitigation structure (NMS) was designed to improve the cooling capacity of the CRR and to counter the pore-filling of the rock layer. Numerical simulations were conducted to evaluate the cooling performance and reinforcing capacity of the NMS based on a developed heat and mass transfer model. The results indicate that the traditional CRR can improve the symmetry of the permafrost subgrade and decrease the ground temperature of shallow permafrost. However, the CRR cannot generate strong enough cooling to influence the deep (below 10 m depth) and warm permafrost with a mean annual ground temperature above −1.0°C. The wind-blown sand can further weaken the cooling of the CRR and cause significant permafrost warming and thawing beneath the slopes, posing a severe threat to the long-term safe operation of the embankment. The proposed NMS can produce a significantly superior cooling performance to the CRR. If the CRR is reinforced by the new structure, it can not only effectively cool the underlying warm permafrost but also elevate the permafrost table. The new structure can also protect the rock layer on the slopes from sand-filling. The NMS can be used as an effective method for roadbed design or maintenance over warm permafrost.